DMSO-Mediated Difunctionalization of Electron-Deficient Olefins to Access β-Hydroxysulfides with High Chemoselectivity - Gao, Bao; Liu, Xiaojun; Yan, Qian; Yang, Ruiting; Jiang, Tao; Zhang, Xiuli (Synthesis, 2022)
A novel and convenient method for the highly chemoselective synthesis of β-hydroxysulfides mediated by DMSO is reported. This eco-friendly reaction was amenable to a broad range of substrates and provided the desired β-hydroxysulfides in moderate to good yields with high selectivity via radical process. Moreover, several pharmaceutical and bioactive molecules were also suitable substrates for this reaction conditions to afford the targeted products in good yields.
Keywords: β-hydroxysulfides; chemoselective synthesis; electron-deficient alkenes; radical process; air atmosphere